Atrial fibrillation and CHA2DS2VASc score of 1 - is there a problem in clinical practice? - E. I. Baranova; V. A. Pavlova; V. A. Ionin; E. Yu. Petrischeva; O. I. Bliznuk; E. L. Zaslavskaya; I. Ma; D. S. Skuridin; E. V. Shlakhto (Российский кардиологический журнал)
Aim. To study the incidence of nonvalvular atrial fibrillation (AF) in patients with a CHA2DS2VASc score of 1 in actual clinical practice, to determine the major and minor risk factors of thromboembolism and the frequency of oral anticoagulant therapy in these patients.Material and methods. We performed a retrospective analysis of 6575 medical records of patients hospitalized for five years in a therapeutic inpatient unit. To determine the stroke risk, major and minor modifying factors were assessed.Results. Of 1160 patients with nonvalvular AF, 93 (8,0%) patients had a CHA2DS2VASc score of 1: hypertension (87,1%), heart failure (4,3%), vascular diseases (4,3%), diabetes (2,15%) and age 65-74 years (2,2%); minor modifying factors were as follows: left atrial (LA) dilatation (81,7%), obesity (40,9%), persistent/permanent AF (37,6%), proteinuria (26,9%), chronic kidney disease (3,2%). A combination of minor risk factors was observed in 61,3%, the most common of which were obesity, LA dilatation, persistent/permanent AF. Anticoagulants were prescribed to 72% of patients with a CHA2DS2VASc score of 1.Conclusion. In actual clinical practice, patients with nonvalvular AF with a CHA2DS2VASc score of 1 are often found. The most common risk factors for stroke in these patients are hypertension, persistent or permanent AF, LA dilatation, and obesity. The use of anticoagulant therapy in these patients does not contradict current guidelines. However, further prospective follow-up is necessary to determine the effectiveness and safety of this therapy.